Lipid-based Nanocarriers for siRNA Delivery: Challenges, Strategies and the Lessons Learned from the DODAX: MO Liposomal System - Oliveira, Ana C. N. (2019)
The possibility of using the RNA interference (RNAi) mechanisms in gene therapy was one of the scientific breakthroughs of the last century. Despite the extraordinary therapeutic potential of this approach, the need for an efficient gene carrier is hampering the translation of the RNAi technology to the clinical setting. Although a diversity of nanocarriers has been described, liposomes continue to be one of the most attractive siRNA vehicles due to their relatively low toxicity, facilitated siRNA complexation, high transfection efficiency and enhanced pharmacokinetic properties. This review focuses on RNAi as a therapeutic approach, the challenges to its application, namely the nucleic acids’ delivery process, and current strategies to improve therapeutic efficacy. Additionally, lipid-based nanocarriers are described, and lessons learned from the relation between biophysical properties and biological performance of the dioctadecyldimethylammonium:monoolein (DODAX: MO) system are explored. Liposomes show great potential as siRNA delivery systems, being safe nanocarriers to protect nucleic acids in circulation, extend their half-life time, target specific cells and reduce off-target effects. Nevertheless, several issues related to delivery must be overcome before RNAi therapies reach their full potential, namely target-cell specificity and endosomal escape. Understanding the relationship between biophysical properties and biological performance is an essential step in the gene therapy field.